Składniki odżywcze i ich rola w diecie sportowca = Nutrients and their role in athlete’s diet - Kalisz, Zdzisława; Juraszek, Karolina; Glama, Ewa; Weber-Rajek, Magdalena; Hoffman, Magdalena; Kalisz, Justyna; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Kalisz Zdzisława, Juraszek Karolina, Glama Ewa, Weber-Rajek Magdalena, Hoffmann Magdalena, Kalisz Justyna, Zukow Walery. Składniki odżywcze i ich rola w diecie sportowca = Nutrients and their role in athlete’s diet. Journal of Education, Health and Sport. 2016;6(8):522-538. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60945 http://ojs.ukw.edu.pl/index.php/johs/article/view/3789 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 26.08.2016. Składniki odżywcze i ich rola w diecie sportowca Nutrients and their role in athlete’s diet Zdzisława Kalisz2, Karolina Juraszek2, 4, Ewa Glama2, Magdalena Weber-Rajek1, Magdalena Hoffmann3, Justyna Kalisz5, Walery Zukow6 1. Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Bydgoska Szkoła Wyższa w Bydgoszczy 3. Uniwersyteckie Centrum Kliniczne w Gdańsku, Klinika Nadciśnienia Tętniczego i Diabetologii 4. Centrum Onkologii im. prof. F. Łukaszczyka w Bydgoszczy, Zakład Rehabilitacji 5. Szpital Uniwersytecki nr 2 im. J. Biziela w Bydgoszczy, Klinika Hematologii 6. Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: składniki odżywcze, dieta, sportowcy. Key words: nutrients, diet, athletes. Streszczenie Składniki pokarmowe pełnią ważną rolę w prawidłowym funkcjonowaniu organizmu ludzkiego. Prowadzony tryb życia ze szczególnym uwzględnieniem aktywności ruchowej, ściśle wiąże się z doborem odpowiednio zbilansowanej diety. Celem badań była ocena odżywiania się sportowców danej dyscypliny sportowej. Badaniem objęto 30 piłkarzy nożnych z klubu sportowego Olimpia Grudziądz, którzy wyrazili chęć wypełnienia ankiety w okresie od marca do maja 2016 roku. Ogólna ocena żywienia piłkarzy uprawiających piłkę nożną jest zadowalająca. Badania wykazały, że piłkarze spożywają posiłek mniej niż 1 godzinę po treningu, czyli odpowiedni czas niezbędny w szybkiej regeneracji glikogenu mięśniowego. Ocena spożywania warzyw i owoców jest nie w pełni prawidłowa, ponieważ są one spożywane w różnej częstotliwości i nie są spożywane codziennie. Racjonalny sposób żywienia sportowców wymaga systematycznego dostarczania organizmowi wszystkich niezbędnych składników odżywczych w ilościach i proporcjach odpowiadających jego potrzebom, a całodzienna racja pokarmowa powinna uwzględniać pięć posiłków w ciągu dnia. Abstract Dietary nutrients play a significant role in the normal function of the body. Life style focused on physical activity necessitates appropriately balanced diet. The goal of this study was to assess the dietary habits of a selected group of athletes. Participants of the study were 30 male football players from the Olimpia Grudziadz athletic club, who, between March and May of 2016, agreed to fill out a questionnaire pertaining to their diets. Based on the compiled data from the questionnaire, the overall diet can be considered well-balanced with minor deficiencies. Participating athletes consume a meal rich in key nutrients within an hour of their training, the optimal time necessary to replenish muscle glycogen. This study revealed, however, that the number of servings of fruit and vegetables is below the recommended daily norm, and the fruit and vegetables are not consumed daily. To maximize performance and ensure rapid recovery necessitates carefully balanced and appropriately timed diet. It is recommended that the daily dietary regimen consists of five evenly spaced meals rich in nutrients that prepare the athlete for the strenuous physical activity and replenish depleted energy stores during recovery period.